Quantifying the Effectiveness of Transformative Islamic Education in Madrasah: a PLS-SEM Perspective - Putri, Adhitya Eka; Setyawan, Herman (Indonesian Journal of Education and Learning, 2025)
Transformative Islamic Education is an approach to Islamic teaching and learning through the development of various aspects including character and moral values as well as the application of Islamic teachings in everyday life to achieve positive and transformative changes in students. This research aimed to investigate the factors influencing the effectiveness of Transformative Islamic Education at Madrasah Aliyah. This research employed an explanatory sequential mixed-method design. Data were obtained from 126 students of Madrasah Aliyah Negeri (MAN) 3 Sleman. The data were then analysed using PLS-SEM and interactive data analysis. The results of the present study show that various factors influence the effectiveness of Transformative Islamic Education, including pedagogical approaches; teacher-student relationships; technology and learning media; and student motivation. Since all those factors have a positive and significant influence on the effectiveness of Transformative Islamic Education, it indicates that the research results can be generalized to the population. Ultimately, this research has implications for devoting efforts to achieve positive and transformative change for students at MAN 3 Sleman.